Rehabilitative of COVID-19 patients with acute lower extremity Ischemia and amputation - Luigia Brugliera; Alfio Spina; Paola Castellazzi; Paolo Cimino; Pietro Arcuri; Maria Grazia Deriu; Chiara Zanetta; Sara Monica Angelone; Jody Filippo Capitanio; Federica Alemanno; Carlo Meloni; Giuseppe D'Angelo; et al. (Medical Journals Sweden, 2020)
Objective: To evaluate the clinical characteristics and rehabilitation management of patients who undergo amputation for COVID-19-associated coagulopathy. Methods: Clinical and laboratory data for 3 patients were analysed and their rehabilitative management discussed. Results: The medical records of 3 patients who had undergone amputation due to acute lower extremity ischaemia and who were provided with rehabilitation in our COVID-19 unit were reviewed. Conclusion: Coagulation changes related to SARS-CoV-2 may complicate recovery from this devastating disease. The rehabilitation management of amputated patients for COVID-19 acute lower extremity ischaemia is based on a multilevel approach for clinical, functional, nutritional and neuropsychological needs. Based on this limited experience, a dedicated programme for this specific group of patients seems advantageous to warrant the best functional outcome and quality of life.